Potensi Serapan Karbon Beberapa Jenis Tanaman pada Ruang Terbuka Hijau Universitas Hasanuddin Makassar - Syamsuddin Millang; Eny Yuniati (Biocelebes, 2010)
This research aim to to know potency of absorbent carbon some type of crop and forest Universitas Hasanuddin Makassar. Perception and measurement to high and the breast high tree diameter to know biomassa conducted with sampling intake. Sum up taken example plot are 6 fruit of the size 20 x 50 m or for the width of 0.1 Ha. Election plot example of conducted in purposive sampling based for consideration of dominant crop type in a body, type composition, and the coronet closeness. For measurement biomassa request conducted by non-destructive sampling namely without destroying sample, while for plant under by destructive sampling or entangle mutilation sample that is by cutting all plant of under which stay in kuadran and given the brought by last lable of the room in order to be known the wet weight and the weight run dry. Result indicate that potency of absorbent carbon vary pursuant to type of crop and its forest group. Sum up biomassa and highest on carbon there are group of forest Ki-Hujan each 156.0 ton/Ha. and 78.0 ton/Ha. and lower is group johar with amount of biomassa and on file C each 38.43 ton/Ha. and 19.22 ton/Ha. Average highest on file carbon there are group of teak;core forest exeed that is equal to 4.03 ton/Ha./year and lower of group of forest johar that is 0.58 ton/Ha./year, while per individual request there are at local mango type equal to 0.06 ton/tree/year and lower at type waru of equal to 0.0004 ton/tree/year. On the total carbon at RTH UNHAS in this time is 8.652,43 ton and potency of carbon fixation of equal to 366.54 ton/years. Key words: Carbon fixation, green air-gap, biomassa.